Contamination of hybrid hernia meshes compared to bioresorbable Phasix™ Mesh in a rabbit subcutaneous implant inoculation model. (October 2019) - Lake, Spencer P.; Stoikes, Nathaniel F.N.; Badhwar, Amit; Deeken, Corey R.
Abstract: Background: Hybrid hernia meshes combine biological tissue-derived extracellular matrix with permanent or resorbable synthetic. The objective of this study was to evaluate hybrid meshes (Gore® Synecor, Zenapro™, Ovitex™ 1S Reinforced Bioscaffold Permanent, and Ovitex™ 1S Reinforced Bioscaffold Resorbable) compared to non-hybrid, bioresorbable synthetic mesh (Phasix™ Mesh) in a rabbit bacterial inoculation model. Materials and methods: Subcutaneous pockets were bilaterally created in male, New Zealand White rabbits (n = 25). Circular meshes (3.8 cm diameter) were implanted and inoculated with 1 × 10 6 colony forming units (CFU) of clinically-isolated methicillin-resistant Staphylococcus aureus (MRSA). A given animal received a single mesh type. Seven days post-inoculation, animals were euthanized and white material and microbial colonization were assessed by abscess scoring and CFU quantification, respectively. Non-parametric Kruskal-Wallis with Dunn's post-hoc tests compared results for different meshes. Results: Phasix™ Mesh and Synecor exhibited significantly lower abscess scores than Zenapro™, Ovitex™ 1S Permanent, and Ovitex™ 1S Resorbable ( p  < 0.05). All pocket swabs for Zenapro™ and Ovitex™ meshes were positive for MRSA (100%), with 20% of Synecor and 0% Phasix™ Mesh. Microbial colonization was significantly lower for Phasix™ Mesh (0 CFU) relative to Zenapro™ (6.73 × 10 7  CFU (median)), Ovitex™ 1S Permanent (7.87 × 10 7  CFU) and Ovitex™ 1S Resorbable (1.45 × 10 8  CFU), and for Synecor (0 CFU) relative to both Ovitex™ meshes. Phasix™ Mesh was the only device with no detectable abscess or microbial colonization. Conclusion: Phasix™ Mesh demonstrated no detectable abscess or microbial colonization at 7-days post-implantation and inoculation, in contrast with four hybrid meshes, which all demonstrated colonization in a rabbit bacterial inoculation model. Highlights: Phasix™ Mesh exhibited no detectable abscess or microbial colonization. 100% of Zenapro™ and Ovitex™ pocket swabs were positive for MRSA. 20% of Synecor pocket swabs were positive for MRSA. Phasix™ Mesh exhibited significantly lower abscess scores than Zenapro and Ovitex. Synecor exhibited significantly lower abscess scores than Zenapro and Ovitex.